Pemberdayaan Guru Melalui Peningkatan Inovasi Belajar Mengajar - Khiyaroh, Intihaul; Raikhan, Raikhan (PARTISIPATORY, 2023)
Community empowerment in Pambon Hamlet through the results of observations and data mining that we conducted for the community for thirty-four days shows various phenomena that occur. There are several aspects that we explored, ranging from the aspects of education, health, economy to social and community in Pambon Hamlet. Seeing the human resources (HR) that are developing in the world of education, we hold a Scientific Discussion: Increasing Teaching and Learning Innovations. This activity is expected to be able to increase the innovation and creativity of teachers in the teaching and learning process through scientific discussions related to teaching and learning innovations with Khoirun Nasikh, M.H.I. as the source.